A Comparative Study on Diagnostic Efficacy of WBC Parameters, Platelet Count, C-Reactive Protein, and Serum Ferritin in Early Onset and Late Onset Neonatal Sepsis - Thakur, Naqsh; Patil, Prakash M; Charki, Siddu; Hippargi, Surekha B (Annals of Pathology and Laboratory Medicine, 2024)
Background Early detection of neonatal sepsis is complicated due to vague symptoms and variations based on gestational age. Rapid identification is vital, and low-cost diagnostic tools like WBC parameters, platelet count, serum ferritin, and C-reactive protein (CRP) can speed up time-sensitive diagnosis. This can mitigate antibiotic resistance and overuse, cutting expenses in underdeveloped regions of India. Material and Methods Ninety cases of neonates <90 days [clinically suspicious admitted cases of early onset (EOS) and late onset neonatal sepsis (LOS): 30 cases each and 30 controls] were selected post-September 01, 2022, for the cross-sectional comparative study. Blood samples were obtained upon clinical suspicion of sepsis, prior to antibiotic treatment, and the above-mentioned parameters were analyzed. Results Preterm births constituted 20% (EOS), 36% (LOS), and 26% (control). Low birth weight occurred in 36% (EOS), 33% (LOS), and 23% (control); females represented 46% (EOS), 53% (LOS), and 53% (control). Culture-positive cases were 14 (EOS) and 19 (LOS). Notable variations emerged in CRP, I/T ratio, and toxic granules. The combined analysis of EOS and LOS indicated CRP's sensitivity at 78%, specificity at 90%, PPV at 94%, and NPV at 68%. I/T ratio exhibited 72% sensitivity, 97% specificity, 98% PPV, and 64% NPV. Toxic granules demonstrated 50% sensitivity, 97% specificity, 97% PPV, and 50% NPV, showcasing their diagnostic potential across various onset patterns. Conclusion For early-onset sepsis, the I/T ratio and toxic granules displayed significant utility, while CRP emerged as a standout performer for late-onset cases. On the whole, CRP emerged as the premier standalone marker, adaptable for pairing in early onset and singly for late onset, with commendable efficacy. Remarkable disparities in ferritin values between septic and non-septic groups call for further exploration of ferritin's diagnostic applicability.